Pengaruh Kesiapan Guru Mengajar dan Motivasi Belajar Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Ekonomi Kelas X SMA Negeri 4 Pematang Siantar - Junita Mariana Pasaribu; Anton Luvi Siahaan; Binsar Tison Gultom (CV Putra Publisher, 2024)
This research aims to determine the influence of teacher readiness to teach and student learning motivation on student learning outcomes in the Class X Economics subject at SMA Negeri 4 Pematangsiantar. The type of research used in this research is quantitative research with an associative approach and research design using a survey design. The population in this study was 72 students. The sample in this study was 72 students. Data collection techniques use observation, documentation, and questionnaires. The data in this study were analyzed using normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression tests, partial tests, simultaneous tests and determinant tests. The research results show that there is an influence of teacher teaching readiness on student Economics learning outcomes with tcount > ttable (2.233 > 1.990). Furthermore, there is an influence of student learning motivation on student Economics learning outcomes with tcount > ttable (2.609 > 1.990). and there is an influence between teacher readiness to teach and student learning motivation on student Economics learning outcomes with Fcount > Ftable (3.783 > 3.110).